REPRESENTASI KEKUASAAN DALAM NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER (REPRESENTATION OF POWER IN THE NOVEL BUMI MANUSIA BY PRAMOEDYA ANANTA TOER) - Oktavia, Tesa (Universitas Lambung Mangkurat, 2024)
AbstractRepresentation of Power in The Novel Bumi Manusia by Pramoedya Ananta Toer. This research describes Norman Fairclough's critical discourse analysis. Descriptive-qualitative is the method utilized in this research. Data analysis uses critical discourse analysis based on text, discourse practice, and sociocultural practice to describe and interpret hidden meanings. This research utilizes note-taking and reading techniques. The data in this study are words in a collection of novels. The results of the research show that there are: 1) In the text part, researchers can find three basic elements, namely, elements of representation, relations and identity. 2) In the discourse practice section, it examines the process of production and consumption of novel texts that are biased by Pramoedya Ananta Toer's profession and life context as an author. 3) The sociocultural practice is divided into three parts, namely situational, institutional, and social.Keywords: Representation, power, novelAbstrakRepresentasi Kekuasaan dalam Novel Bumi Manusia Karya Pramoedya Ananta Toer. Penelitian ini mendeskripsikan analisis wacana kritis Norman Fairclough. Deskriptif-kualitatif merupakan metode yang dimanfaatkan pada penelitian ini. Penganalisisan data menggunakan analisis wacana kritis berdasarkan teks, discourse practice, dan sociocultural practice untuk menguraikan dan menginterpretasikan makna yang tersembunyi. Penelitian ini memanfaatkan teknik catat dan baca. Data pada penelitian ini berupa kata dalam kumpulan novel. Hasil penelitian menunjukkan adanya: 1) Pada bagian teks peneliti dapat menemukan tiga elemen dasar yaitu, unsur representasi, relasi dan identitas. 2) Pada bagian discourse practice meneliti proses produksi dan konsumsi teks novel yang terbias dari profesi dan konteks kehidupan Pramoedya Ananta Toer sebagai pengarang. 3) pada bagian sociocultural practice terbagi menjadi tiga bagian, yaitu situasional, institusional, dan sosial.Kata-kata kunci: representasi, kekuasaan, novel